TACKLING THE COVID-19 IN INDONESIA THROUGH DISCOURSE: THE REVIEW OF MODALITY IN NEWS - Nita Maya Valiantien; Ririn Setyowati (Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
Employing the data from selected English news from the official website of Cabinet Secretariat of The Republic of Indonesia (www.setkab.go.id), we analyzed the use of modal verbs as the indicator of modality. The findings show four modal verbs that indicate epistemic modality and deontic modality. For epistemic modality, we found the function of expressing possibility or probability which is signed by the use of modal will and can. Meanwhile, for deontic modality, the functions that we found are obligation and permission. Obligation is expressed by the use of must and should, meanwhile for permission, it is signed by modal verb can.